Internal Factor Analysis of Hotel, Restaurant, and Company Stock Prices Tourism on the Indonesia Stock Exchange - Meisa Najunda Putri (Sekolah Tinggi Manajemen IPMI, 2022)
The objective of the study is to analyse the effect of Leverage, Profitability, and Market Value on Stock Prices. The study used quantitative approach in which the population were hotel, restaurant, and tourism companies listed on the Indonesia Stock Exchange (IDX). Non-probability sampling method is used to collect 41 hotel, restaurant, and tourism companies. Panel data regression analysis method use Eviews 11.0 program to test the hypothesis. This study showed that Leverage measured by Debt to Equity (DER) has no effect on Stock Prices, Profitability is measured by Return on Equity (ROE) has a positive effect on Stock Prices, and Market Value is measured by Price Earnings Ratio ( PER) has no effect on shares prices. Keywords: leverage, profitability, market value, and stock price.